Influence of negative bias voltage on microstructure and property of Al-Ti-N films deposited by multi-arc ion plating. Issue 4 (March 2017) - Cai, Fei; Chen, Mohan; Li, Mingxi; Zhang, Shihong
Abstract: In this study, we systematically investigated the effects of negative bias voltage on the composition, deposition efficiency, microstructure, and mechanical properties of multi-arc ion plated (MAIP) AlTiN films. The films were deposited on high-speed steel substrates by MAIP at various negative bias voltages. The results indicated that the Al content [ Al/(Al+Ti) ratio] and the deposition efficiency were significantly altered by the application of negative bias voltages. X-ray photoelectron spectroscopy analysis showed that the AlTiN films were composed of Ti–N and Al–N bonds. The macroparticles (MPs) on the film surface decreased with increasing negative bias voltage. We also discussed the different types of MPs found on the films and their influence on the process of determining the hardness of the films. The microhardness of the films depends on the negative bias voltages. The films deposited at −250 V exhibited a maximum hardness of 45 GPa. The adhesion and frictional tests revealed that the film deposited at −150 V demonstrated the highest cracking resistance, the best adhesion under a critical load of 78 N, highest adhesion strength, and the lowest and stablest coefficient of friction at 0.23.